FUNGSI TUTURAN EKSPRESIF DALAM FILM NGERI-NGERI SEDAP SUTRADARA BENE DION - Kiki Widyawati; Asnawi (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
Expressive language is not only used in direct communication between individuals, but it also appears in films through dialogues between characters. These dialogues are based on real-life communication, which typically occurs between speakers and their addressees. The movie "Ngeri-Ngeri Sedap" features many dialogues that reveal the psychological attitudes of the characters. Films can be used as a medium to express functions of speech acts, such as expressive speech acts. The purpose of this research is to describe the issues and analyze the data clearly about the function of expressive speech acts in inter-character dialogues in the movie "Ngeri-Ngeri Sedap" directed by Bene Dion. The results of the study are used to develop language studies and increase reading materials related to expressive language in the field of pragmatic studies, thereby supporting reference sources for future research. The theory used in this research is the expressive speech act function proposed by Searle. The approach used is a qualitative approach with the content analysis method. The data in this study are verbal data (spoken) or all speeches in the dialogue spoken by characters in the movie "Ngeri-Ngeri Sedap" directed by Bene Dion. The data source in this research is the movie "Ngeri-Ngeri Sedap" directed by Bene Dion. The data collection technique used is observation, listening, and note-taking. The data analysis technique used is content analysis or descriptive content analysis. From the study, 75 speeches were identified as expressive speech acts. The functions of expressive speech acts found are praising, apologizing, thanking, criticizing, complaining, blaming, and praising.